THE QUESTIONS OF DETERMINATION AND THE FORMS OF PREVENTING OF THE PLAGIARISM - Зуєва, Вікторія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article explores the issues of defining plagiarism, academic plagiarism and the form of preventing plagiarism. Research methods: theoretical analysis of the concept of «plagiarism», «academic plagiarism», a comparative analysis of the essential features of this type of copyright infringement in domestic and foreign legislation. The types of plagiarism are classified. Discussion: the problems of plagiarism and academic plagiarism in the works of students and scientists, the classification of its species, the development of forms its prevention in Ukraine.